Role of paramagnetic chromium in chromium(VI)-induced damage in cultured mammalian cells. - Sugiyama, M (1994)
Chromium(VI) compounds are known to be potent toxic and carcinogenic agents. Because chromium(VI) is easily taken up by cells and is subsequently reduced to chromium(III), the formation of paramagnetic chromium such as chromium(V) and chromium(III) is believed to play a role in the adverse biological effects of chromium(VI) compounds. The present report, uses electron spin resonance (ESR) spectroscopy; the importance of the role of paramagnetic chromium in chromium(VI)-induced damage in intact cultured cells is discussed, based upon our studies with antioxidants including vitamin E (alpha-tocopherol), B2 (riboflavin), C (ascorbic acid), and so on. These studies appear to confirm the participation of paramagnetic Cr such as chromium(V) and Chromium(III) in chromium(VI)-induced cellular damage.